Cost effectiveness modelling for health technology assessment : a practical course /: a practical course. (2015) - Edlin, Richard; McCabe, Chris (Christopher J.), 1967-; Hulme, Claire; Hall, Peter; (Information specialist), Wright, Judy
No abstract available